2021
DOI: 10.3390/jcm10184255
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Sensory Processing in Dichotic Listening of Young Adults with Listening Difficulties

Abstract: Previous studies have suggested that varying attention demands in dichotic listening (DL) tasks might be a clinically feasible method to distinguish ‘bottom-up’ from ‘top-down’ deficits in listening. This study aims to investigate DL processing in adults with listening difficulties (LD). We assessed the performance of a listening difficulties group (LDG) (n = 24, mean age = 24, backward digit span = 4.0) and a control group (CG) (n = 25, mean age = 29.2, backward digit span = 6.4) in DL tests involving non-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recent studies have also reported poor cognition, such as attention and working memory, in individuals with LiD [Roebuck and Barry, 2018;Magimairaj et al, 2018;Pascoinelli et al, 2021;Petley et al, 2021], however, they do not adequately describe the actual state of poor attention ability in adults with LiD. Hence, one aspect revealed in this study was that adults with LiD had difficulties in distributing their attention properly to many things.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have also reported poor cognition, such as attention and working memory, in individuals with LiD [Roebuck and Barry, 2018;Magimairaj et al, 2018;Pascoinelli et al, 2021;Petley et al, 2021], however, they do not adequately describe the actual state of poor attention ability in adults with LiD. Hence, one aspect revealed in this study was that adults with LiD had difficulties in distributing their attention properly to many things.…”
Section: Discussionmentioning
confidence: 59%
“…Findings may lead to better understanding the role of sensory modulation in parental scaffolding of children, from both perspectives—modeling as well as co-regulation [ 16 ]. While previous reports indicated that sensory modulation and anxiety are related [ 56 , 93 , 94 ], sensory modulation and executive functions have also been reported to co-occur, affecting emotional regulation, self-control, and daily activities [ 87 , 88 , 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participant is asked to verbally reproduce either all the perceived signals (free recall) or only those perceived in one ear (directed attention). Attention plays an important part in DL tests, and is considered as a source of variance in DL results [ 3 , 4 ]. Attentional manipulations were used in dichotic listening studies to control for attentional bias; Asbjornsen et al proposed an index of attentional shift (The Attentional Shift Index (ASI)) based on the ratio of correct responses and intrusion errors when the subject is performing the tasks of directed attention [ 4 ].…”
Section: Introductionmentioning
confidence: 99%